Pengelolaan Program Pendidikan Kesetaraan Kejar Paket C Di PKBM Setia Budi Kabupaten Pati - Devy Amalia Nur Fitriah; Sungkowo Edy Mulyono (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The aim of this research is to describe the implementation of program management and determine the supporting and inhibiting factors for equality education pursuing package C at PKBM Setia Budi, Pati Regency. The research method used was qualitative descriptive research with participants: 1 PKBM Chair, 2 PKBM staff, 2 Pursue Package C tutors, 2 learning residents. Data collection techniques use observation, interviews and documentation. Data validity techniques use source triangulation and technical triangulation. Data was analyzed through the stages of data collection, data reduction, data presentation, as well as conclusions and verification. The results of the research show that the management process of the equality education program pursuing package C at PKBM Setia Budi, Pati Regency is carried out through the stages of planning, organizing, implementing, monitoring and evaluating. Planning in management includes program planning and implementation plans. Organization in management includes the division of tasks and roles of each administrator. Implementation in management includes the learning process and infrastructure. Supervision in management includes internal supervision and external supervision. Evaluation in management includes program evaluation and learning evaluation. Supporting factors include the community's need for equal education which is still high and there is support from the government and society. Meanwhile, inhibiting factors include low levels of student attendance, limited budgets, and inadequate infrastructure. The conclusion from this research is that the implementation process for managing the equality education program pursuing package C includes planning, organizing, implementing, monitoring and evaluating. The researcher's suggestion is that the learning media used can be made more innovative and varied so that students are more motivated to attend learning.